Discriminación en la regulación peruana del descanso por maternidad y paternidad - Ulloa Millares, Daniel (2019)
Labor laws have always sought to protect women, especially when they are mothers. Regardless, the majority of these rules originate in a paternalistic supposition and without gender perspective, maintaining a stereotyped image of the woman in her role as a mother, without the correction of the inadequate situation in which they live. This article seeks to present a juridical opinion about current normative situation, the recent corrections and the existing problems, accompanied by proposals of possible solutions.